Horror of the Anthropocene: American Ecohorror Since 1945 - BOURKE, EMILY (Trinity College Dublin. School of English. Discipline of English, 2019)
This thesis explores the evolution of environmental anxiety in American horror fiction and film, arguing that the subgenre most commonly referred to as “ecohorror” merits reassessment in the face of global warming’s changing contexts. Greater awareness of the multifarious threats emerging from our environment means that it no longer suffices to consider plants, animals, and landscapes to be ecohorror’s only subjects. Much as ecocriticism initially limited itself in its focus on “obviously” environmental subjects, so critical approaches to ecohorror have tended to overemphasise the importance of the “revenge of nature” plot, and missed opportunities to explore other terrors bound up in our current age of ecological catastrophe. Tracing the subgenre from the 1950s to the present day, this thesis tracks the changing face of ecohorror, examining a range of texts that demonstrate the influence of environmentalist thought on American fiction and film across the decades.
APPROVED
Keywords: horror; ecohorror; american studies; environment